1994
DOI: 10.1083/jcb.126.5.1157
|View full text |Cite
|
Sign up to set email alerts
|

The cytoplasmic domain mediates localization of furin to the trans-Golgi network en route to the endosomal/lysosomal system.

Abstract: Abstract. To investigate the mechanisms of membrane protein localization to the Golgi complex, we have examined the intracellular trafficking of epitope-tagged forms of the mammalian endopeptidase, furin, in stably transformed rat basophilic leukemia cells. Our studies show that furin is predominantly localized to the trans-Golgi network (TGN) at steady state, with smaller amounts present in intracellular vesicles. Biochemical and morphological analyses reveal that furin is progressively delivered to a lysosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
186
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(206 citation statements)
references
References 62 publications
19
186
1
Order By: Relevance
“…A SmaI/XhoI restriction fragment containing the fulllength receptor was ligated into pCIneo expression vector. pCDM8.1 expression vector (Invitrogen) encoding the interleukin-2 receptor ␣-subunit (tac) fused in frame with the transmembrane and cytoplasmic domain of furin (tac-furin) was kindly provided by Dr. Juan Bonifacino (19). The pEYFP-Golgi vector encoding the enhanced yellow fluorescent protein fused to the N-terminal 81 amino acids of the precursor to human ␤-1,4 galactosyltransferase was obtained from CLONTECH.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A SmaI/XhoI restriction fragment containing the fulllength receptor was ligated into pCIneo expression vector. pCDM8.1 expression vector (Invitrogen) encoding the interleukin-2 receptor ␣-subunit (tac) fused in frame with the transmembrane and cytoplasmic domain of furin (tac-furin) was kindly provided by Dr. Juan Bonifacino (19). The pEYFP-Golgi vector encoding the enhanced yellow fluorescent protein fused to the N-terminal 81 amino acids of the precursor to human ␤-1,4 galactosyltransferase was obtained from CLONTECH.…”
Section: Methodsmentioning
confidence: 99%
“…The chimera consisted of the extracellular domain of the ␣ subunit of the interleukin-2 receptor fused to the transmembrane and cytoplasmic domains of furin (19). It has previously been shown that both native furin and the tac-furin chimera are localized predominantly in the TGN.…”
Section: Fig 11 Expression Of Snx15 Impairs Post-translational Procmentioning
confidence: 99%
“…The molecular mass of the AP-4 complex was calculated on the basis of its Stokes radius and sedimentation coefficient, assuming a partial specific volume of 0.72-0.75 cm 3 /g (24). Immunofluorescence Microscopy-HeLa cell monolayers were grown on glass coverslips and in some cases treated with brefeldin A or transiently transfected with HA epitope-tagged constructs of TGN38 or furin (7,25). Cells were fixed in methanol/acetone (1:1, v/v) for 10 min at Ϫ20°C and subsequently air-dried.…”
Section: Methodsmentioning
confidence: 99%
“…5). Localization of furin to the TGN requires a bipartite motif that is composed of the casein kinase 2 (CK2)-phosphorylated acidic cluster (EECPpSDpSEEDE, where p highlights the serine residues that are phosphorylated) and a membrane-proximal segment containing two hydrophobic motifs (YKGL and LI) [23][24][25][26][27] (FIG. 5).…”
Section: Localization To the Trans-golgi Networkmentioning
confidence: 99%